Saving young lives using plant-based ready-to-use therapeutic food - Yoshida, Makiko (2022)
Makiko Yoshida CONFERENCE The 8th Tokyo International Conference on African Development (TICAD8) Side Event: How Japan’s know-how can help address Africa’s food and nutrition challenges: Interventions and impacts SEP 28, 2022 - 6:00 TO 7:30PM JST